The Unique Genetic and Histological Characteristics of DMBA-Induced Mammary Tumors in an Organoid-Based Carcinogenesis Model - Naruse, Mie; Ishigamori, Rikako; Imai, Toshio (Frontiers in Genetics, 2021)
Here, we report a model system using in vitro 7,12-dimethylbenz[a]anthracene (DMBA; 0.6 μM)-treated mammary tissue-derived organoids generated from heterozygous BALB/c-Trp53 knockout mice to induce tumors after injection into the nude mouse subcutis. In parallel, a single oral dose of DMBA (50 mg/kg bodyweight) to the same murine strain induced mammary adenocarcinomas, characterized by biphasic structures differentiated into luminal and myoepithelial lineages and frequent Hras mutations at codon 61. In the present study, the genetic and histological characteristics of DMBA-induced tumors in the organoid-based model were evaluated to validate its similarities to the in vivo study. The organoid-derived tumors were low-grade adenocarcinomas composed of luminal and basal/myoepithelial cells. When the organoid-derived carcinomas were passaged to other nude mice, they partly progressed to squamous cell carcinomas (SCCs). Whole exome sequencing revealed no mutations at Hras codon 61 in the organoid-derived tumors. However, various mutations were detected in other genes such as Tusc3 and Tgfbr2, which have been reported as cancer-associated or homeostatic squamous cell genes. The most common mutational pattern observed in these genes were the G:C to T:A transversions and G:C to A:T transitions, which are not typical of the mutations caused by DMBA treatment. In conclusion, DMBA exhibited carcinogenicity in the both the ex vivo and in vivo mammary carcinogenesis models, albeit with distinct histological and genetical alterations. Further studies are needed to clarify whether organoid-based carcinogenesis models generated following chemical treatment in vitro could be applied to the clarification of the novel mode of action of chemical carcinogenesis.